What do we know about the effects of landscape changes on plant–pollinator interaction networks? - Ferreira, Patrícia Alves; Boscolo, Danilo; Viana, Blandina Felipe (Ecological indicators, 2013)
Biotic interactions play an important role on the organization and persistence of biodiversity. Unnatural modifications of landscape structure such as habitat loss and fragmentation can isolate populations and disrupt biological communities, affecting species survival and altering the complex set of relationships between plants and pollinators. Plant–pollinator interaction networks have characteristics such asymmetry and nestedness that may influence the stability and robustness of networks to landscape changes. Species in mutualistic networks might respond to landscape modifications with a sudden collapse at critical habitat destruction thresholds. In this work we review general trends in the scientific literature related to the effects of landscape changes on plant–pollinator networks. For this, a survey in Scopus and Web of Knowledge databases was conducted in May 2011 using all seven possible combinations of the terms “pollinat*” with the terms “landscape”, “habitat loss” and “network”. We found 155 papers and 92% of those showed significant effects of landscape changes on pollinator diversity and plant reproductive success. Approximately 50% of all analyzed papers showed effects of agriculture intensification as a result of increases in the conversion of natural areas into agricultural crops on plant–pollinator interactions. Landscape modifications affected cross-pollination and the sexual reproduction of plants largely because of reduced diversity and availability of pollinators due to increased habitat isolation and reduction of floral resources and nesting areas in the remaining available habitat. An integrated approach concerning the effects of modified landscapes on natural ecosystems regarding how these variations can affect the stability and robustness of pollination networks can be extremely useful for conservation of plant–pollinators interactions, with positive overall consequences for conservation of plant, pollinators and pollination services in natural and agricultural ecosystems.